Studia z geografii średnich miast w Polsce : problematyka Tarnowa : opracowanie zbiorowe = Studies in geography of medium-size cities = Issledovaniâ po geografii gorodov srednej veličiny v Pol'še - Dziewoński, Kazimierz (1910–1994). Red.; Kiełczewska-Zaleska, Maria (1906–1980). Red.; Iwanicka-Lyrowa, Elżbieta. Red. (IGiPZ PAN, 1971)
274 s., [4] k. tabl. złoż. : mapy, wykr., err. ; 24 cm
Bibliogr. przy pracach
Streszcz. ang. i ros.
Keywords: Geografia miast -- Polska -- Tarnów (województwo małopolskie) [KABA]; miasta średnie; funkcje miast; struktura przestrzenna miast; Tarnów

Wybory Prezydenta RP w 2010 roku: studium znaczenia elektoratu dużych i średnich miast = Polish presidential election in 2010: A study of the power of voters in big and medium-sized towns - Matykowski, Roman; Kulczyńska, Katarzyna (IGiPZ PAN, 2010)
24 cm
Keywords: miasta duże; miasta średnie; elektoralne typy miast; geografia wyborcza; wybory prezydenckie; elektorat; Polska

Formation of a new structure of socio-spatial differentiation in the towns of Pomerania: The case study of three medium-sized towns - Szymańska, Wioletta (IGiPZ PAN, 2013)
24 cm
Keywords: struktury społeczno-przestrzenne; przestrzeń wewnątrzmiejska; miasta średnie; Pomorze; Lębork; Szczecinek; Wałcz

UHI effect in the city of Padua: simulations and mitigation strategies using the Rayman and envimet model - Noro, Marco; Busato, Filippo; Lazzarin, Renato (IGiPZ PAN, 2014)
The UHI phenomenon was studied in a medium size city in the North-East of Italy and the results are reported in this paper. Experimental measurements were carried out during the summer of 2012, measuring the main thermo-hygrometric variables by mobile survey and also the mean radiant temperature in characteristic sites of the city area: the historic centre, high and low density populated residential zones, the industrial zone and the rural zone. Two simulation models were used in order to calculate the effect of some mitigation strategies on UHI intensity and outdoor thermal comfort indexes for four typical days of the year.
24 cm
Keywords: miasta średnie; średnia temperatura promieniowania; strategia łagodzenia; symulacje zewnętrznego komfortu cieplnego; miejska wyspa ciepła

Are medium-sized cities strong nodes in the settlement system? Demographic trends of Italian provincial capitals from 2000 to the Covid-19 pandemic - Clerici, Maria Antonietta. Autor (IGiPZ PAN, 2022)
Medium-sized cities are an important component of the settlement system and are often described as a joining link between urban and rural areas. However, in recent decades they have been impacted by growing competition from large cities which have tremendous appeal for the post-Fordist economy and for various segments of the population. This paper analyses the demographic trajectories of 99 medium-sized cities in Italy with provincial capital status, from the beginning of the twenty-first century to the outbreak of the COVID-19 pandemic. Over a twenty-year period marked by many difficulties for the Italian economy in an international context, what has the demographic performance of these cities been? The research addresses two areas. On the one hand, it analyses the demographic vitality of the provincial capitals compared to the metropolitan centres; on the other, it follows the redistribution of populations in the provincial capitals’ urban areas, which coincide with the employment areas (Sistemi locali del lavoro). Significant behavioural discontinuities emerge between the decade of 2000-2010 and the following decade, which was characterised by a gradual recovery after the shock of the Great Recession. The picture was changed further by the COVID-19 pandemic. Furthermore, persistent differences between the medium-sized cities of Northern and Southern Italy stand out, but so do new internal divisions within the country, reframing this historical dualism.
24 cm
Keywords: miasta średniej wielkości; stolice prowincji; dynamika demograficzna; obszary zatrudnienia; Wielka Recesja; COVID-19; Włochy

The role of locality and place-specific development paths in creating smart cities: The example of middle-sized Hungarian cities - Szalai, Ádám. Autor; Fabula, Szabolcs. Autor (IGiPZ PAN, 2021)
Smart cities have spawned a global discourse, which is, however, dominated by notions and theories originating from major metropolis regions in the Global North/West, as well as by quantitative approaches. Drawing on case studies from Hungary, this paper aims to reveal how place-specific factors influence smart-city development and to discover the characteristics of this development in the Hungarian context. For this purpose, qualitative research methods, namely a content analysis of policy documents and semi-structured expert interviews, were used. Based on the results, we distinguished four development paths: representative, stalled, organizational model, and focused smart city. Findings broaden the general understanding of smart-city development, providing policy recommendations for the future adaptation of the concept.
24 cm
Keywords: inteligentne miasto; Węgry; studium przypadku; kontekst lokalny i globalny; miasta średniej wielkości

Przegląd Geograficzny T. 45 z. 2 (1973) (IGiPZ PAN, 1973)
24 cm
Keywords: nauki geograficzne; teoria geografii; geografia polska; geografia stosowana; bioproduktywność Ziemi; stożki ablacyjne; lodowce polarne; albedo; ruchy masowe; doliny rzeczne; dolina Wisły; miasta średnie; Islandia; Irak; Polska